Comparison of Modified Mallampati Classification and Thyromental Height to Predict Difficult Intubation - Tayyeba Aslam, Taoseef Ahmed, Ali Kashif, Hana Khurshid, Sibgha Zafar, Samina Ashraf, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Difficult intubation is an emergency situation that an anaesthetist come across frequently. It is a frequent cause of mortality in practice of anesthesia. Mallampati classification (MPC) of the oropharyngeal structures is a simple test to assess anticipated difficult airway for endotracheal intubation. thyromental height (TMH) test is now also commonly used to predict difficult intubation. Objective: To evaluate diagnostic accuracy of modified mallampati classification and thyromental height using Cormack and Lehane's classification of laryngoscopy as a gold standard. Study Design: Descriptive cross sectional validation study. Setting: Department of Anaesthesia, Benazir Bhutto Hospital, Rawalpindi. Duration: 20-Sep-2021 to 19-Mar-2022. Material and Methods: A total number of 1035 were included in this study. Pre-operatively modified Mallampati test (MMT) and TMH test was performed. Mallampati class III and IV were considered difficult. While TMH height >50 mm was considered as difficult intubation. Difficult intubation equipment’s was ready, i.e. stylet, boogie, LMA, I-gel. General anaesthesia was induced in the operating room after collecting baseline vital signs. After three minutes, a skilled anesthesiologist performed a laryngoscopy while the patient was sniffing. To validate the diagnosis of difficult intubation, the laryngeal view was appraised using a modified Cormack and Lehane (C-L) grading system. Results: Mean age of patients was 40.16±12.19 years. Mean height of patients was 152.94±8.32 cm, mean weight was 65.01±13.59 Kg and Mean body mass index (BMI) was 27.78±5.64 kg/m2. There were 768 (74.20%) males and 267 (25.80%) females. TMH was 77.8% sensitive, 94.6% specific having 70.0% PPV, 96.3% NPV and 92.27% accuracy. On diagnostic accuracy of MMP taking difficult intubation according to standard as gold standard, MMP was 92.4% sensitive, 90.1% specific having 60.2% PPV, 98.6% NPV and 90.3% accuracy. Practical implications: Thyromental Height (TMH) needs more broad usage in multiple settings to be validated as a single most important predictor of difficult laryngoscopy. It will thus be used widely all over the country rendering fewer complications for the patients. Conclusion: TMH was the test that was most sensitive and accurate at foretelling difficult laryngoscopy when compared to the modified Mallampati score. TMH has potential as a single anatomical metric to predict the possibility of a difficult laryngoscopy. Keywords: Mallampati classification, thyromental height, Cormack and Lehane's classification, laryngoscopy.